National Estimates of hospital emergency department visits due to acute injuries associated with hookah smoking, United States, 2011-2019 - Naa A. Inyang; Joanne T. Chang; Baoguang Wang (BMC, 2020)
Abstract Introduction Hookah (also known as waterpipe) smoking is associated with acute adverse health effects such as vomiting and fainting, symptoms related to carbon monoxide poisoning, and decreased pulmonary function, however, national estimates of hookah-related acute injuries are not currently available in the scientific literature. This study provides national estimates of United States hospital emergency department visits due to hookah-related acute injuries. Methods We analyzed 2011-2019 data from the National Electronic Injury Surveillance System to calculate national estimates of emergency department visits due to hookah-related acute injuries. National Electronic Injury Surveillance System data were gathered from approximately 100 United States hospitals selected as a probability sample of approximately 5000 hospitals with emergency departments. Each case contains information abstracted from all emergency department records involving injuries associated with consumer products. All individuals admitted to emergency departments who sustained hookah-related acute injuries were included in the study. Results During 2011-2019, an estimated 1371 (95% confidence interval: 505-2283) United States hospital emergency department visits were related to hookah-related acute injuries. The most common injuries were sustained from dizziness/light-headedness and syncopal episodes (54.8%), followed by burns (41.5%). Young adults aged 18-24 years accounted for 66.8% of hookah-related acute injuries admitted to United States emergency departments. Conclusions This study provides national estimates of hospital emergency department visits due to hookah-related acute injuries. We found that hookah smoking related AIs mostly occurred among young adults. Study findings may inform public health policy and educational intervention efforts to prevent these events and complement other acute injury surveillance systems, such as the National Poison Data System.